Zarządzanie należnościami w procesie kreowania wartości przedsiębiorstwa - wyniki badań - Szymański, Piotr (Trade Receivables Management as a Process of Creating Enterprise Value - Results of Research, 2007)
The article contains survey results for current trade receivables management and value based management in 191 enterprises from south-western Poland. This research consists of 82 questioners and 1734 financial statements from 1991 until 2003. The study proves that too many Polish enterprises destroy their value. One of the main reasons is weakness of current trade receivables management. In this study the companies were divided in three groups. The first group involved enterprises which created value for shareholders, the second group included enterprises which destroyed value for shareholders and the third one involved enterprises about which it was difficult to say if they created or destroyed value for shareholders. The comparison shows that enterprises from the first group better manage current trade receivables than other groups.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 550-569